2016
DOI: 10.1177/1074248416644987
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Carvedilol Compared to Nebivolol on Insulin Resistance and Lipid Profile in Patients With Essential Hypertension

Abstract: New generation beta-blockers, carvedilol and nebivolol, efficiently and similarly decrease blood pressure. They have similar favorable effects on glucose, insulin, IR, and the lipid profile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
1
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 15 publications
2
7
1
5
Order By: Relevance
“…Three previous studies have also reported a neutral effect of nebivolol on HDL cholesterol levels, [26][27][28] and two studies even reported a reduction in HDL cholesterol levels. 29,30 In the present study, nebivolol treatment lowered HDL cholesterol levels and seemed to attenuate the effect of rosuvastatin on increasing HDL cholesterol levels. Reasons for the different results among studies could not be clarified as the treatment schedule and inclusion criteria were quite different.…”
supporting
confidence: 49%
“…Three previous studies have also reported a neutral effect of nebivolol on HDL cholesterol levels, [26][27][28] and two studies even reported a reduction in HDL cholesterol levels. 29,30 In the present study, nebivolol treatment lowered HDL cholesterol levels and seemed to attenuate the effect of rosuvastatin on increasing HDL cholesterol levels. Reasons for the different results among studies could not be clarified as the treatment schedule and inclusion criteria were quite different.…”
supporting
confidence: 49%
“…A few studies elucidated the more favourable side effect profile of nebivolol. Ozyildiz et al compared carvedilol and nebivolol in different metabolic parameters and found both drugs to have favourable effects on blood glucose, insulin sensitivity and total cholesterol levels.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with DM treated with long-term beta-blocker have recently been evaluated by a prospective observational study, as well as a post hoc analysis from the ACCORD study, suggesting increased all-cause death in DM patients treated with beta-blockers 40,41 . Carvedilol and nebivolol may be preferred because of their ability to improve insulin sensitivity, with no negative effects on glycemic control 42,43 .…”
Section: Specific Cardiovascular Therapiesmentioning
confidence: 99%